TEACHERS’ CHALLENGES IN IMPLEMENTING AN INDEPENDENT LEARNING CURRICULUM IN SCIENCE AND SOCIAL STUDIES FOR PRIMARY IV STUDENTS - Inayah Septiyani; Sukartono (Universitas Majalengka, 2023)
This study aims to describe the challenges faced by teachers in implementing the independent learning curriculum in natural and social science learning for fourth grade students at SD N 02 Wonorejo. The focus in this study is to discuss the challenges faced by teachers while planning, implementing, and evaluating natural and social science lessons. This research uses a qualitative approach with a phenomenological design. Sources of research data are teachers and fourth grade students and school principals. This research was carried out in semester two of the 2022/2023 school year. Data collection techniques with observation, interviews, and documentation. Validity test using source and method triangulation. The data analysis technique used Miles and Huberman's interactive analysis with the stages of data reduction, data presentation, and conclusions. This research concludes that there are challenges faced by teachers in the stages of planning, implementing, and evaluating learning. Teachers' challenges in natural and social science learning include obstacles in determining learning strategies and models, difficulties in reducing learning outcomes to learning objectives, not understanding the format in detail in making teaching modules, there are no student books yet, the use of learning media is not maximized, difficulties in linking science material with social, and techniques in carrying out the assessment have not been maximized. Thus, it becomes an evaluation that it is necessary to maximize learning by knowing the various challenges in implementing the independent curriculum in natural and social science learning. Penelitian ini bertujuan untuk mendeskripsikan tantangan yang dihadapi guru dalam penerapan kurikulum merdeka belajar pada pembelajaran IPAS siswa kelas IV SD N 02 Wonorejo. Fokus dalam penelitian ini yaitu membahas mengenai tantangan apa saja yang dihadapi oleh guru selama menyusun perencanaan pembelajaran, melaksanakan pembelajaran, dan mengevaluasi pembelajaran IPAS. Penelitian menggunakan pendekatan kualitatif dengan desain fenomenologi. Sumber data penelitian yaitu guru dan siswa kelas IV serta kepala sekolah. Penelitian ini dilaksanakan pada semester 2 tahun pembelajaran 2022/2023. Teknik pengumpulan data dengan observasi, wawancara, dan dokumentasi. Uji keabsahan menggunakan triangulasi sumber dan metode. Teknik analisis data menggunakan analisis interaktif Miles dan Huberman dengan tahap-tahap reduksi data, penyajian data, dan kesimpulan. Penelitian ini menyimpulkan bahwa terdapat tantangan yang dihadapi guru pada tahap perencanaan, pelaksanaan, dan evaluasi pembelajaran. Tantangan guru pada pembelajaran IPAS antara lain terkendala dalam menentukan strategi dan model pembelajaran, kesulitan dalam menurunkan CP menjadi tujuan pembelajaran, belum paham format secara detail dalam membuat modul ajar, belum terdapat buku siswa, pemanfaatan media pembelajaran belum maksimal, kesulitan dalam mengaitkan materi IPA dengan IPS, dan teknik dalam melaksanakan asesmen belum maksimal. Dengan demikian, menjadi sebuah evaluasi bahwa perlu memaksimalkan pembelajaran dengan mengetahui berbagai tantangan dalam menerapkan kurikulum merdeka pada pembelajaran IPAS.